2009
DOI: 10.2298/zmspn0917087k
|View full text |Cite
|
Sign up to set email alerts
|

Screening of mycotoxins in animal feed from the region of Vojvodina

Abstract: This paper shows the results of screening of mycotoxins in animal feed originating from the region of Vojvodina. Permanent screening is needed on all levels of production and storage, as well as the use of known methods to reduce mould contamination or toxin content in feedstuffs and feed. A total of 56 representative samples were collected from feed companies from the region of Vojvodina. Samples were collected during February 2009. The collected samples included 41 samples of feedstuffs (soybean, soybean mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In 70 cow's milk samples, Polovinski-Horvatović et al (2010) used TLC method after immunoaffinity column clean-up to determine AFM1 and have found that none were contaminated with AFM1 in concentration greater than 0.05 µg/kg. Lower occurrence of AFM1 contamination reported in these reports from Serbia, compared to the results obtained in this and subsequent studies, can be explained with the absence of AFs in maize and other feed material in Serbia in previous years (Kokić et al, 2009;Jakšić et al, 2011;. In all the reports, ELISA test kit was used for AFs determination.…”
Section: Discussionmentioning
confidence: 56%
“…In 70 cow's milk samples, Polovinski-Horvatović et al (2010) used TLC method after immunoaffinity column clean-up to determine AFM1 and have found that none were contaminated with AFM1 in concentration greater than 0.05 µg/kg. Lower occurrence of AFM1 contamination reported in these reports from Serbia, compared to the results obtained in this and subsequent studies, can be explained with the absence of AFs in maize and other feed material in Serbia in previous years (Kokić et al, 2009;Jakšić et al, 2011;. In all the reports, ELISA test kit was used for AFs determination.…”
Section: Discussionmentioning
confidence: 56%
“…Typically, AFB 1 is not found in fishmeal because its matrix is unsuitable for the production of mycotoxin. It has been presented that AFB 1 was not detected in any fishmeal samples [ 32 ]. However, fishmeal contaminated with AFB 1 has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Contamination of aquaculture feeds and naturally contaminated experimental fish feeds with the mycotoxins AFB 1 , ZEN, DON, FB 1 , T-2 and OTA reported in the literature (according to the studies ofBoonyaratpalin et al 2001;Kokic et al 2009;Deng et al 2010;Huang et al 2011;Rajeev Raghavan et al 2011;Pietsch et al 2013;Greco et al 2015) …”
mentioning
confidence: 99%